Statistik Deskriptif Keputusan Pembelian Konsumen Melalui Branding Produk - Sani Rusminah; Muhamad Taufik (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
During the pandemic, public interest in cycling has increased. The impact of cycling on society in Indonesia can also be seen from the sales aspect. Compared to the previous year, bicycle sales in 2020 increased by 40%. Of this increase, the most prominent is public interest in imported bicycles, one of which is Canyon. In Indonesia itself, there are various kinds of bicycle brands, ranging from imported or local components, with various models and price ranges. Therefore, it is necessary to make efforts from Canyon producers to increase purchase intention in Canyon bicycle products.